Pengaruh Inovasi Produk, Persediaan Barang dan Peran Word of Mouth Terhadap Keputusan Pembelian di UD. Combi Prima Grafika Babat – Lamongan - Ahmad Irfan Ardiansyah; Betty Rahayu; Hasannudin Nursalim Putra (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to determine whether product innovation, inventory, and word of mouth influence purchasing decisions at UD. Combi Prima Grafika Babat - Lamongan. The type of research used is quantitative research with a survey method. Data were obtained through a questionnaire published to 100 consumer respondents of UD. Combi Prima Grafika who have shopped more than once, with selection using a purposive sampling technique. The findings of this study indicate that product innovation and word of mouth have a positive and significant influence on purchasing decisions. However, inventory does not show a positive and significant influence on purchasing decisions. Overall, product innovation, inventory, and word of mouth have a significant influence on consumer purchasing decisions at UD. Combi Prima Grafika. From the results of this study, it can be concluded that it is important for UD. Combi Prima Grafika to continue to improve product innovation, especially in terms of relevant designs in accordance with existing trends, as well as improving inventory management to ensure sufficient stock. These improvements are expected to increase customer satisfaction, strengthen positive word of mouth promotions, and ultimately encourage increased purchasing decisions and sales.